Caracterización preliminar de cultivares comerciales de sorgo silero en Misiones (Argentina). Campaña 2016/2017 - Fariza, Silvina Ines; Heck, Mónica Isabel; De Lucia, Adrían Darío; Blaszchik, Jorge Ariel (EEA Cerro Azul, INTA, 2021)
Fodder reserves allow intensification and stabilization of pastoral production systems by transferring pasture and green surpluses to times of the year when the supply is lower. Given the limited local information on the behavior of sorghum crop, the present work aims to characterize and identify genotypes and / or groups of genotypes with better aptitude for the production of whole plant silage for the region. A total of 13 sorghum cultivars were evaluated using phenological, morphological and agronomic traits. Significant differences between cultivars for plant height, days to flowering, green and dry matter production and percentage of stem and panicle were found. A great variation in the behavior of the evaluated materials was observed, with flowering cycles between 90 and 131 days and plant heights from 1.89 to 3.78 m. The average production of green and dry biomass was 60.687 kg ha-1 and 21.215 kg ha-1 respectively. The photosensitive cultivars G130 AA and ADV 2010 showed the greatest potential of accumulation of green and dry matter. However, the cultivar Sugargraze, besides the high biomass accumulation presents a greater contribution of the panicle, which could improve the quality of silage. The agronomic potential observed in this study shows sorghum as an excellent alternative for the region.